Afterword: Moral Experience in Anthropology. (March 2014) - Csordas, Thomas J.
Abstract The concept of moral experience offers an important dimension to anthropological thinking about morality, particularly when one distinguishes between approaches that treat specific sociocultural loci of moral experience and those that address conditions of possibility for moral experience. A coherent approach to morality should also reconsider earlier works in order to avoid the embarrassment of reinventing the wheel in our work. I take a step in this direction by juxtaposing two works from 1950s American anthropology, the analysis of Hopi ethics by Richard Brandt and the Navajo moral code by John Ladd. This exercise leads us to interrogate the validity of construing morality as a cultural system at that period in comparison to the status of those societies today, to other small‐scale societies in colonial or postcolonial situations, and to complex societies such as those of contemporary Euro‐America. Juxtaposing moral experience and moral code highlights the relative contributions of cultural analysis of morality from first‐person and third‐person perspectives, offers a step toward identifying the presence of a moral ambience akin to the emotional ambience designated by the concept of ethos, and leads toward a phenomenological concern with moral being and becoming and recognition of care as essential to the moral domain.